IMPLEMENTASI MANAJEMEN PERKANTORAN BERBASIS BUDAYA MUTU DALAM MEWUJUDKAN LEMBAGA PENDIDIKAN ISLAM UNGGUL - Edi Ahyani; M Sahrawi Saimima (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2023)
Education is a barometer for the progress of a nation. Or simply put, the progress of a state or nation lies in its education. This research examines Office Management, Office Management Based on Quality Culture and Quality Culture of Superior Islamic Educational Institutions. The research method used is qualitative research with library research methods. In this research process, the Implementation of Quality Culture-Based Office Management in Realizing Superior Islamic Educational Institutions, its management is carried out through the stages of planning, organizing, initiating and  directing operations, by having a cultural basis for the quality of superior programs in it, having a vision and mission that can be realized by all elements in the Islamic Educational Institution in a measurable manner and focused on customer needs, have adequate facilities, as well as the creation of responsibility for all elements in the organization with values that are still fought for in their duties or work and the latter have the principle of loyalty to the organization.Keywords : Management, Quality Culture, Islamic Education